bumdes management in improving economy in molutabu village kabila bone sub-district bone bolango district: pengelolaan bumdes dalam meningkatkan ekonomi di desa molutabu kecamatan kabila bone kabupaten bone bolango - mohamad langi; imam mashudi (LP2M Universitas Bina Mandiri Gorontalo, 2023)
ABSTRACT Mohamad Langi NPM. 1220191037. BUMDes Management in Improving the Economy of the Molutabu Village Community, Kabila Bone District, Bone Bolango Regency. D-III Office Administration Study Program Supervisor I Imam Mashudi, S.Pd., M.Pd and Fitriyani Husain, S.Pd., M.Si Supervisor II. The purpose of preparing the Final Project Report is to find out how the process of managing BUMDes in Molutabu Village, Kabila Bone District, Bone Bolango Regency, the role of the village government and community participation in improving the community's economy in Molutabu Village, and to find out the inhibiting factors in the implementation process. The data were obtained by observation and interviews and then processed in presenting the data to conclusions using qualitative methods and descriptive approaches. The results show that the role of the Village Government to increase community participation in improving the community's economy in Molutabu Village can be concluded quite well. The inhibiting factor in realizing the economic improvement of the Molutabu Village community was caused by the limited knowledge of the management who felt there was a need for improvement. Keywords: Economic Improvement, BUMDes, Molutabu